1999
DOI: 10.1099/00222615-48-8-731
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Characterisation of Secreted Phospholipase Activities from Cryptococcus Neoformans in their Naturally Occurring State

Abstract: A recent study demonstrated that phospholipase B (PLB), lysophospholipase (LPL) and lysophopholipase transacylase (LPTA) are secreted by Cryptococcus neoformans var. neoformans and showed that the amount of enzyme production correlated with virulence in mice. The present study characterised the extracellular enzyme activities further by radiometric assays and 31 P nuclear magnetic resonance spectroscopy (NMR). All three enzymes were most active between 25 and 40OC. Bovine lung surfactant and its major lipid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…4 show that raft-associated PLB activity increased approximately 15-fold following raft disruption. This was not due to stimulation of enzyme activity, since the detergent concentration in the assay was Ͻ0.1%, a concentration at which we have shown previously causes no stimulation of PLB activity (8,40). In contrast, only a fivefold increase in PLB activity was obtained following disruption of nonraft membranes.…”
mentioning
confidence: 80%
“…4 show that raft-associated PLB activity increased approximately 15-fold following raft disruption. This was not due to stimulation of enzyme activity, since the detergent concentration in the assay was Ͻ0.1%, a concentration at which we have shown previously causes no stimulation of PLB activity (8,40). In contrast, only a fivefold increase in PLB activity was obtained following disruption of nonraft membranes.…”
mentioning
confidence: 80%
“…Analysis of four cryptococcal strains with various levels of phospholipase activity revealed a correlation between phospholipase activity and virulence in BALB\c mice [22]. We also showed that phospholipid components of lung surfactant and cellular membranes were targets for C. neoformans phospholipases in their natural state [24]. Vidotto et al subsequently suggested that phospholipase production by C. neoformans may be linked to capsule size [25].…”
Section: Introductionmentioning
confidence: 88%
“…The respective roles of extracellular PLB, LPL and LPTA activities in human cryptococcal infection may vary in specific microenvironments within the host. We have previously shown that the LPL and LPTA activities of the native enzyme can reacylate lysophospholipids and reverse damage caused to neutrophils by other components secreted by cryptococci [24]. The ability to degrade (PLB) membrane phospholipids may promote invasion of lung tissue, whereas the ability to repair (LPL\LPTA) the phospholipids may enable cryptococci to parasitize phagocytes without eliciting an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted enzyme, phospholipase B (Plb1), 2 is an established cryptococcal virulence determinant (1). It facilitates invasion of host lung tissue (2), most likely by hydrolyzing phospholipids in mammalian cell membranes and pulmonary surfactant (3)(4)(5)(6) and is essential for hematogenous dissemination of infection (2). In the cryptococcal cell, Plb1 is localized in specialized membrane domains known as rafts (7).…”
mentioning
confidence: 99%